PERKEMBANGAN KESEJAHTERAAN PENDUDUK DI PROVINSI PAPUA - Ulah Tri Wibowo; Tukiran Tukiran (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2003)
There is a disparity in welfare between the people who dwell in mountanous areas and those living in plains, coastalal areas which is due to the difference in accessibility. Coastal regions, develop fast and generally have higher economic and social well-being because of the better accessibility they are bestowed with. However, in general, the people of Papua enjoy lower welfare than they are capable of enjoying in relation to the natural resopurces the province has. The abundant natural resources in the province have not been exploited to the full in endevor to improve the well being of the popuakltuion. The division of Papua province into West Papua, Central Papua, and East Papua is expected to accelerate the development process, which should in turn reduce income disparity. None theless, some redress must be found to the problem of uneven distribution of natural resources among the three provinces, to prevent the emergence of regional paracholiasm which may the source of income inequality among the three new provinces due to their different respective locations on the the coast, plains, and mountaneous region.